Infinitely repeated game based real-time scheduling for low-carbon flexible job shop considering multi-time periods. (20th February 2020) - Wang, Jin; Yang, Jiahao; Zhang, Yingfeng; Ren, Shan; Liu, Yang
Abstract : Production scheduling has great significance for optimizing tasks distribution, reducing energy consumption and mitigating environmental degradation. Currently, the research of production scheduling considering energy consumption mainly focuses on the traditional manufacturing workshop. With the wide application of the Internet of Things (IoT) technology, the real-time data of manufacturing resources and production processes can be retrieved easily. These manufacturing data can provide opportunities for manufacturing enterprises to reduce energy consumption and enhance production efficiency. To achieve these targets, a multi-period production planning based real-time scheduling (MPPRS) approach for the IoT-enabled low-carbon flexible job shop (LFJS) is presented in this study to carry out real-time scheduling based on the real-time manufacturing data. Then, the mathematical models of real-time scheduling are established to achieve production efficiency improvement and energy consumption reduction. To obtain a feasible solution, an infinitely repeated game optimization approach is used. Finally, a case study is implemented to analyse and discuss the effectiveness of the proposed method. The results show that in general, the proposed method can achieve better results than the existing dynamic scheduling methods. Highlights: Infinitely repeated game method was used to reduce real-time scheduling's complexity. Production planning layer was used to generate new scheduling as a production planning. Real-time scheduling layer was used to finish operations from production planning layer. Applying real-time data can timely reduce the influence of exceptions.